Genetic generalized epilepsy: factors associated with drug resistance polytherapy - Hassan Hosny; Nervana Elfayoumy; Mahmoud Adly; Hend Abdelghany (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery, 2023)
Abstract Background Different studies investigating generalized genetic epilepsy (GGE) have shown that achieving 5 years of remission, early seizure remission, and needing antiseizure medication (ASM) monotherapy may predict favorable long-term outcomes. Results This is a retrospective analytical cohort study. Records of patients with GGE diagnoses at a large epilepsy center in Cairo served as the data source. 630 patients (297 male patients (47.1%) and 333 female (52.9%)) were included, their median onset age was 13 years. The follow-up period of this study was at least 4 years. 418 patients (66.1%) were early remitters, 160 patients (25.4%) were late remitters, and 52 patients (8.3%) were intractable. In addition, 367 patients (58.3%) needed a single ASM to achieve a maximum remission period (monotherapy group), while 263 patients (41.7%) needed ASM polytherapy. Stepwise regression analysis revealed that absence seizures, clusters of seizures, seizure frequency before treatment, and dose of sodium valproate (VPA) until the first remission were independent predictors for polytherapy. Moreover, absence seizures, seizure frequency before treatment, VPA dose, and catamenial seizures in females were independent predictors of intractability. Conclusion The majority of GGE have a favorable outcome, some clinical features could predict the need for polytherapy and failure of remission on treatment.